Manajemen Perpustakaan SMP Sukma Bangsa Lhokseumawe - Zulkhairi, Zulkhairi; Nurasiah, Nurasiah (CV. Lentera Literasi Indonesia, 2025)
This study aims to provide a comprehensive description of library management at SMP Sukma Bangsa Lhokseumawe, covering aspects of planning, organizing, implementing, and evaluating library services in supporting the learning process. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and document studies. The results show that library management has been carried out in accordance with modern management principles, including planning collections relevant to the curriculum, organizing human resources and facilities, and implementing services oriented toward the needs of students and teachers. Evaluations are conducted periodically to ensure service quality and collection development. However, several challenges were identified, such as budget limitations and the suboptimal use of technology. This study recommends increasing the budget, providing librarian training, and optimizing the use of information technology to improve the effectiveness of library management. With proper management, the library is expected to serve as a learning resource center that supports the achievement of educational goals at SMP Sukma Bangsa Lhokseumawe.